2020
DOI: 10.1177/2055668320950195
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the privacy of technology users who have cognitive disabilities: Identifying areas for improvement and targets for change

Abstract: Introduction Information Technologies (IT) may serve assistive roles that facilitate the interaction of people living with cognitive disabilities (CD) within their environments. However, there are some notable concerns related to privacy threats associated with the use of IT. The purpose of this study was to examine how assistive technology developers may best adapt over time to develop their IT to be resilient against threats to privacy. We therefore focused on the following areas: (1) developers’ knowledge a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…The characteristics of the research are summarized in Table 1. Overall, the studies referred to finding barriers in the accessibility and cognitive accessibility fields when using digital services [20][21][22][23][24][25][26]. The study participants varied in each study.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The characteristics of the research are summarized in Table 1. Overall, the studies referred to finding barriers in the accessibility and cognitive accessibility fields when using digital services [20][21][22][23][24][25][26]. The study participants varied in each study.…”
Section: Resultsmentioning
confidence: 99%
“…In most of the studies, the participants were people with some kind of disability and identified as social groups. The study participants were mentally disabled persons [20], cognitive disabilities persons [24], technology developers and students [21,26], visually impaired persons [23] and intellectually disabled persons [22,25]. The studies' subjects varied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations